A plant nutrient study on a dark red latosol under cerrado vegetation - Britto, Dirce P. P. de Souza; Castro, Abeilard Fernando de; Mendes, Waldemar; Jaccoud, Alcy; Ramos, Doracy Pessoa; Costa, Francisco Ademar (Pesquisa Agropecuaria Brasileira, 2014)
The field experiments were conducted on a dark red latosol under cerrado vegetation located in the Colégio Agrícola of the Federal District of Brasília. Nitrogen, phosphorus and potassium and lime were combined with Cu, Zn, Mn, B and Mg. The test crops were corn, soybeans and cotton. A randomized block was used, consisting of nine treatments and six replications. Three of the six replications received magnesium. Corn and cotton gave the best response to an application of NPK + B + Mo + Mn and Zn. Similar results were obtained from soybeans when the inoculation of the seeds were considered as an addition of nitrogen. It was concluded that when the micronutrients were applied with NPK only zinc gave a favorable response. Responses to applications of magnesium were not consistant for all crops. Based on the results of the previous studies one experiment was conducted to determine the optimum level of zinc. Two levels of NPK were combined with four levels of zinc. The highest production was obtained with an application of 90 kg N, 150 kg P2O5, 120 kg K2O and 10 kg zinc sulphate per hectare.